Clinical in‐situ evaluation of the effect of rubber dam isolation on bond strength to enamel. Issue 1 (2nd November 2022) - Falacho, Rui I.; Melo, Eliana Azevedo; Marques, Joana A.; Ramos, João Carlos; Guerra, Fernando; Blatz, Markus B.
Abstract: Objective: To evaluate the effect of rubber dam isolation on shear bond strength of two different adhesive systems to enamel. Materials and Methods: The mesial, distal, lingual, and vestibular enamel surfaces of thirty human third molars were prepared (total n = 120). A custom splint was made to fit a volunteer's maxilla, holding the specimens in place in the oral cavity. Four composite resin cylinders were bonded to each tooth with one of two bonding agents (OptiBond FL and Prime&Bond active) with or without rubber dam isolation. Shear bond strength was tested in a universal testing machine and failure modes were assessed. Significance level for statistical analyses was set at 5%. Results: All pairwise comparisons revealed statistical differences ( p < 0.05). The highest mean shear bond strength values were obtained in rubber dam experimental groups, regardless of the adhesive system. Group OptiBond FL with rubber dam presented the highest mean bond strength values. Fracture modes for specimens bonded without rubber dam isolation were adhesive and cohesive within enamel, while rubber dam experimental groups revealed only cohesive fractures. Conclusions: Absolute isolation with rubber dam increases bond strength to enamel, independent of the adhesive system. The three‐step total‐etch system OptiBond FL provided significantly higher bond strength values than Prime&Bond active under both experimental conditions. Clinical Significance: Rubber dam isolation has a significant effect on bond strengths to enamel, independent of the adhesive system. Its application is, therefore, advised whenever adhesive procedures are performed. A filled three‐step etch‐and‐rinse adhesive performed superiorly, with or without rubber dam isolation, when bonding to enamel compared to an isopropanol‐based universal adhesive.